Characterization of coal char surface behavior after a heterogeneous oxidative treatment. (15th December 2017) - Wang, Zhuo-Zhi; Sun, Rui; Ismail, Tamer M.; Xu, Jie; Zhang, Xing-Zhou; Li, Yu-Peng
Highlights: JN and SH coal were used to study the variation of char surface in oxidation reaction. TPD and FT-IR results conveyed that the properties of stable complexes were identified. JN and SH have identical chemical structure on char surface during oxidation reaction. Char conversion ratio had little effect on the distribution of Cwea /Cstr . Abstract: Two typical types of bituminous coal (JN and SH) were employed for thorough devolatilization, then the samples were functionalized by O2 at 1073 K to different conversion ratios (JN: 0.21, 0.34, 0.40, 0.53 and 0.63; SH: 0.15, 0.22, 0.32, 0.42 and 0.52) before the surface oxygen containing complexes C(O) were qualitatively and semi-quantitatively characterized by Fourier transform infrared spectroscopy (FT-IR) and temperature programmed desorption (TPD). A deconvolution method was applied to analyze the C(O) adsorption in the spectral region of 1800–1000 cm −1 in the FT-IR spectra, and the results indicated that the type and thermal stability of these functional groups were as follows: carboxylic (1250 K) < phenol (1350 K) < ether/anhydride (1550 K) < lactone/quinone (1650 K). The TPD results demonstrated that more active sites were generated on the particle surface after the oxidative treatment under O2 atmosphere, especially the samples with low conversion degree (J2, S2, and S3), coal type and conversion ratio had small effects on the ratios of metastable stable complexes to stable complexes Cwea (O)/Cstr (O) under the experimental conditions. The oxidized char samples were significantly more reactive than the raw char, and per unit mass of each oxidized sample could reduce more NO than raw char during the temperature programmed reduction (TPR) process, and phenol, ether and anhydride were the main reactants participated in the NO reduction reaction under high-temperature condition (1173–1600 K).